Gamma radiation synthesis and characterization of colloidal Al-Ni and Al-Cu bimetallic nanoparticles - Abedini, Alam (2012)
The last two decades have seen remarkable progress in nanoscience and nanotechnology particularly in the synthesis of metal nanomaterials, aiming at finding better materials that have desired physical and chemical properties from enhancement of the surface and quantum confinement effects. Intermetallic aluminides such as Al-Ni and Al-Cu bimetallic nanoparticles have attractive properties for examples low densities, high strength and stiffness at elevated temperatures, strong resistances to mechanical, corrosion, acids and alkalis, and outstanding catalytic activity. They are of significant for wide potential applications in pigments, catalysts, and absorbents for Al-Cu bimetallic nanoparticles and in turbine blades, automobile engines, aircraft,electricity generation, and anode electrode materials for Al-Ni bimetallic nanoparticles. Such impressive characteristics and applications of Al-Ni and Al-Cu bimetallic nanoparticles have led us to research their functional systems with the objectives to synthesize Al-Ni and Al-Cu bimetallic nanoparticles and characterize their morphological and crystal structures, optical properties, and reduction mechanism by examining the influence of absorbed dose and initial precursors concentration on the yield, particle size, size distribution, and conduction band energy of the synthesized nanocrystals. Colloidal Al-Ni and Al-Cu bimetallic nanoparticles may be synthesized using various methods, including the chemical, photochemical, electrochemical, sonochemical, and radiolytic reduction techniques. Of these techniques, the radiation-induced synthesis offers additional benefits over the other conventional methods because it produces fully reduced and highly pure bimetallic nanoparticles with free from by-products or reducing agents, and is capable of controlling the particle size. In this work, colloidal Al-Ni and Al-Cu bimetallic nanoparticles were synthesized by gamma irradiation technique in aqueous solutions containing metal chlorides as precursors, polyvinyl alcohol (PVA) as a capping agent, isopropyl alcohol as a radical scavenger of hydroxyl radicals, and distilled water as a solvent. The initial precursor concentrations were between 3.5×10-5 and 4.5×10-5mol/mL for AlCl3 and between 1.5×10-5 and 1.9×10-5mol/mL for both NiCl2 and CuCl2 with Al/Ni and Al/Cu mole ratios of 20/80, 30/70, 50/50, 70/30, and 80/20. All the samples were irradiated with 1.25-MeV 60Co gamma rays at absorbed doses from 50 to 100 kGy for colloidal Al-Ni nanoparticles and from 60 to 120 kGy for colloidal Al-Cu nanoparticles. Gamma rays interact with matter in aqueous solution to produce secondary electrons, which induced reactive species such as solvated electrons and radicals by hydrolysis of water. These electrons and radicals are strong reducing agents that reduce metal ions into zero-valent atoms, the mechanism controlled by the redox potentials of the ions before the atoms agglomerated to form metal nanoparticles. The formation Al-Ni and Al-Cu bimetallic nanoparticles were characterized by energy dispersive X-ray spectroscopy (EDX), powder X-ray diffractometer (XRD), transmission electron microscopy (TEM), and UV-visible absorption spectrometry. The XRD, TEM, and absorption analyses confirmed the formation of Al–Ni bimetallic alloy nanoparticles at all mole ratio, Al-Cu bimetallic alloy nanoparticles at lower Al/Cu molar ratio, and a mixture of Al-Cu bimetallic and bimetallic core-shell nanoparticles at higher Al/Cu mole ratio. The TEM analysis for particle size and size distribution revealed that the average particle size of Al-Ni and Al-Cu bimetallic nanoparticles decreased with the increase of absorbed dose and increased with the increase of precursor concentrations. The average diameter d decreases exponentially with dose D and increases exponentially with precursor concentration C can be represented by an empirical equation ⁄ and (⁄ ) respectively.The smallest particle sizes of 4.4 and 3.7 nm have been achieved for Al-Ni and Al-Cu nanoparticles respectively, which were obtained at the lowest precursor concentration and the highest absorbed dose. At higher doses, the amount of nucleation is more than unreduced ions and smaller particle sizes are produced. On the other hand, at lower doses nucleation events are less than the total initial metal ions and large particle sizes are produced owing to the fact that metal nanoparticles can be ionized again into larger ions before the metal ions reduce into larger metal nanoparticles by solvated electrons. At higher precursor concentrations the amount of unreduced ions is more than the amount of nucleation induced by radiation and larger particle sizes are produced. The optical absorption spectra reveal that the absorption peaks blue shifted from 391 to 377 nm with the increase of dose from 50 to 100 kGy for Al-Ni nanoparticles and from 580 to 576 nm with the increase of dose from 60 to 120 kGy for Al-Cu nanoparticles,owing to a decrease of particle size with increasing dose. It was confirmed by the TEM measurements. This quantum confinement effect permits the conduction band energy increases from 3.17 to 3.29 eV for Al-Ni nanoparticles and from 2.139 to 2.154 eV for Al-Cu nanoparticles with decreasing particle sizes. In conclusion, it was found that the absorbed dose and the precursors’ molar ratio and concentration are key parameters to influence the composition, crystalline structure, particle size, size distribution, and optical properties the final products of colloidal Al-Ni and Al-Cu bimetallic nanoparticles stabilized in PVA. This is because the competition between nucleation, growth, and agglomeration processes in the formation of nanoclusters during and after irradiation by 1.25 MeV gamma rays.